Difficulties related to medication therapy for anxiety disorder - Ligiane Paula da Cruz; Kelly Graziani Giacchero Vedana; Bruna Paiva do Carmo Mercedes; Adriana Inocenti Miasso (Universidade Federal de Goias, 2016)
This study aimed to comprehend difficulties of people with anxiety disorder referred to follow a medication therapy. This is a cross-sectional descriptive study with a qualitative approach, developed in 2012 with 32 people attended in an ambulatory service at the interior of São Paulo state - Brazil. The data was collected by semi-structured interview recorded and submitted to thematic content analysis. The difficulties to follow pharmacotherapy were represented by the categories: "To have insufficient knowledge about the diagnosis and medication therapy", "To be unsatisfied with the treatment effects", "To wish more than a prescription", "To present fears and worries related with the treatment" and "To identify impediments to follow the medication prescription". This study identified aspects subject to intervention, through interventions focused in listening, education, autonomy and abilities for safety in the use of prescribed medications.